2014
DOI: 10.1038/ejhg.2013.295
|View full text |Cite
|
Sign up to set email alerts
|

Structural and numerical changes of chromosome X in patients with esophageal atresia

Abstract: Esophageal atresia with or without tracheoesophageal fistula (EA/TEF) is a relatively common birth defect often associated with additional congenital anomalies such as vertebral, anal, cardiovascular, renal and limb defects, the so-called VACTERL association. Yet, little is known about the causal genetic factors. Rare case reports of gastrointestinal anomalies in children with triple X syndrome prompted us to survey the incidence of structural and numerical changes of chromosome X in patients with EA/TEF. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…One girl with partial duplication of exons 2-6a was born small for gestational age [Benito-Sanz et al, 2011], which is a known cause of short stature [Rogol and Hayden, 2014]. Two additional small for gestational age babies with SHOX duplication and complex malformations resembling VACTERL association have been described, but their postnatal growth pattern was not shown [Brosens et al, 2014]. Phenotype may be LWD (47%), mainly in partial duplications, or isolated short stature (53%) in both complete and partial duplications, as in the present case ( table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One girl with partial duplication of exons 2-6a was born small for gestational age [Benito-Sanz et al, 2011], which is a known cause of short stature [Rogol and Hayden, 2014]. Two additional small for gestational age babies with SHOX duplication and complex malformations resembling VACTERL association have been described, but their postnatal growth pattern was not shown [Brosens et al, 2014]. Phenotype may be LWD (47%), mainly in partial duplications, or isolated short stature (53%) in both complete and partial duplications, as in the present case ( table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is not always true in individuals with microduplications of PAR1 involving SHOX or its regulatory sequences. In fact, cases with tall, normal and short stature have been reported [Roos et al, 2009;Thomas et al, 2009;D'haene et al, 2010;Iughetti et al, 2010;Benito-Sanz et al, 2011;Brosens et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EA/TEF can also be part of the VACTERL or VATER association, an acronym that refers to the nonrandom occurrence of V ertebral defects, A nal atresia, C ardiac , T racheo‐ E sophageal fistula, R enal and L imb defects (Nora & Nora, 1975; Solomon, 2011; Temtamy & Miller, 1974). The etiology of nonsyndromic EA/TEF is still unknown, a variety of genetic (Brosens, de Jong, et al, 2014; Shaw‐Smith, 2006) and environmental (Felix et al, 2008; Mc Laughlin, Hajduk, Murphy, & Puri, 2013) factors have been proposed. While familial isolated EA/TEF cases have been infrequently reported (Pletcher, Friedes, Breg, & Touloukian, 1991), large studies have shown a very low recurrence risk for isolated EA/TEF among first degree relatives (Bartels et al, 2012; Choinitzki et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Several previous reports also explored the co‐occurrence of chromosomal anomalies among children with gastrointestinal defects (Best et al, ; Brosens et al, ; Felix et al, ; Harris et al, ; Hemming & Rankin, ; Shaw‐Smith, ; Takahashi et al, ; Torfs et al, ). Table also includes the median of the state prevalence estimates of more common chromosomal anomalies (i.e., trisomies 13, 18, and 21, Turner syndrome, and 22q11.2 deletion syndrome) by gastrointestinal defect.…”
Section: Gastrointestinal Defects Results and Discussionmentioning
confidence: 99%